OPTIMIZATION OF ZOTERO AND MENDELEY SOFTWARE TO REFERENCE MANAGEMENT FOR NURSING STUDENTS - Erlina Hermawati; Atik Aryani; Lut Fika Daru Azmi (Universitas Sahid Surakarta, 2023)
Papers or scientific work reports are a form of assignment that is usually given by a lecturer to students. A good paper must of course be in accordance with the rules of good and correct writing, one of which must meet the rules in writing citations or reference sources. Writing references can be done manually or by using certain software to assist the citation process. Some software that is often used is Zotero and Mendeley. This PKM activity aims to provide information and practice how to use Zotero or Mendeley software in managing references, including writing citations in a paper or scientific report. This PKM activity was held for two days, November 21-22 2022 and was attended by 29 participants from the Sahid University Surakarta Bachelor of Nursing Study Program. The results of this PKM activity show that students' knowledge increases after being given training on using Zotero and Mendeley in managing references, and students are able to practice using one of the software to write down references or citations in a paper report.